OFICINAS TEMÁTICAS E O ENSINO DE CIÊNCIAS DA NATUREZA EM UMA ESCOLA DO CAMPO DO MUNICÍPIO DE SANTA MARIA, RIO GRANDE DO SUL - Schlottfeldt, Luciane Maffini (2018)
Country schools (CS) aim at the students’ permanence in the rural environment, providing a type of teaching focused on their life experiences. In relation to the knowledge of the Natural Sciences (NS), this could be mediated through concrete activities such as Thematic Workshops (TW) identified with the reality of rural communities. This study was developed in the context of the Postgraduate Program in Teaching Science and Mathematics of the Franciscan University, in the Line of Research “Teaching and Learning in Science and Mathematics”. The main objective of this paper was to investigate how the four TW developed in Escola Municipal de Ensino Fundamental Intendente Manoel Ribas (EMEFIMR), located in the municipality of Santa Maria, Rio Grande do Sul (RS), were aligned with the teaching of science as it is developed in a CS. Specifically, this study aimed: to study the official guidelines and scientific productions about the public policies of CS as well as the teaching of NS in Elementary School; understand the course of EMEFIMR as a CS in the municipal school network of Santa Maria, RS; analyze the presence of NS in the TW developed at that school; and contribute to the formalization of TW focused on the teaching of science in a CS. A qualitative, bibliographical and documentary research was developed. Official documents made available by the Ministry of Education and Culture, by the Municipality of Education in Santa Maria, RS and by EMEFIMR were analyzed. Initially, a preliminary analysis of the documents, i.e., the Pedagogical Political Project (PPP), the planning of the teachers’ didactic-pedagogical organization and the photographic records of the TW developed in the CS was carried out. Then, the information that was aligned with the area of NS was compiled. The analysis of the data was based on the Content Analysis method, as proposed by Bardin (2016), in which two pre-established categories were chosen, i.e.: i) the didactic proposals listed for the teaching of NS, considering the initiatives for the introduction and qualification of NS in the school by means of TW, and ii) the thematic units and objectives expected for the teaching of science. Both the thematic axes of the NS area and the objectives outlined to reach such axes were analyzed through the TW. The TW are concrete didactic activities, which are relevant to CS and aligned with the teaching of NS, since they provide the students with the observation and implementation of actions in order to improve their view towards the environment in which they live (landscaping, recycling, reuse). Therefore, TW contribute to both recycling and reuse of materials, thus aiming at sustainability and entrepreneurship as a result of the manufacture of products that can be marketed. However, there are some gaps in relation to the scientific approach since, despite the potential offered by the experiences with TW, scientific concepts have rarely been articulated with their proposals. In this case, it would be necessary to look at the teaching plans and objectives of each workshop to better organize them both didactically and pedagogically. Thus, in light of what was found along this research and as a way to enhance initiatives such as TW in terms of methodology, a product was developed to contribute as a didactic resource to the teaching of sciences in CS. That is, the systematization of the TW, based on the following topics: theme, general objective, objects of knowledge, justification, areas of knowledge involved, development and systematization of activities and corresponding information.